2020
DOI: 10.1039/c9cc09827e
|View full text |Cite
|
Sign up to set email alerts
|

Light-controlled cooperative catalysis of asymmetric sulfoxidation based on azobenzene-bridged chiral salen TiIV catalysts

Abstract: Azobenzene-bridged chiral salen TiIV catalysts enabled the cooperative bimetallic catalysis of asymmetric sulfoxidation in a light-controllable way through the E/Z photoisomerism of an azobenzene linker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 30 publications
0
36
0
9
Order By: Relevance
“…For instance, Fu provided that azo would gradually transform from trans to cis isomers under 254 nm irradiation, which could generate discrepant physical and chemical properties for an extended catalytic performance. 7 Besides, Zhu identified that coumarin in the polymer PEO 43 -b-P(DEA 94 -stat-CMA 5 ) could be cross-linked and dimerized by illumination of 365 nm UV light. The chemical changes help to generate a robust copolymer microsphere which could be employed as a carrier for loading guest molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Fu provided that azo would gradually transform from trans to cis isomers under 254 nm irradiation, which could generate discrepant physical and chemical properties for an extended catalytic performance. 7 Besides, Zhu identified that coumarin in the polymer PEO 43 -b-P(DEA 94 -stat-CMA 5 ) could be cross-linked and dimerized by illumination of 365 nm UV light. The chemical changes help to generate a robust copolymer microsphere which could be employed as a carrier for loading guest molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Azo and coumarin are typical photo-responsive groups that are frequently used in smart polymers to trigger reversible structural changes for particular enhanced capabilities. For instance, Fu provided that azo would gradually transform from trans to cis isomers under 254 nm irradiation, which could generate discrepant physical and chemical properties for an extended catalytic performance . Besides, Zhu identified that coumarin in the polymer PEO 43 - b -P­(DEA 94 - stat -CMA 5 ) could be cross-linked and dimerized by illumination of 365 nm UV light.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Arylazopyrazoles (AAP) have been recently introduced as a new class of photo-switchable molecules that exhibit advantages over existing systems. [13][14][15][16] Similar to azobenzenes, 9,12,[17][18][19] AAPs can change their E/Z configuration by photoisomerization using 520 nm visible or 365 nm UV light, [20][21][22] but are considered as superior analogues to azobenzene derivatives because of their high photostationary states of >90% for switching in both directions and their remarkably long thermal half-life times. 18,23,24 Depending on the system under investigation, the light-induced changes of the contact angle Θ vary to a large extend.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–salen catalyzed epoxide hydration is believed to follow a second-order, cooperative bimetallic pathway (bimetallic means that two separate metal salen complexes work together to catalyze the PO hydration reaction). , Compared with the bimetallic reaction mechanism, monometallic mechanism is demonstrated to be unfavorable , and thus is not considered here. Cooperative bimetallic catalysis is of utmost importance in chemical synthesis, where two metal centers work synergistically to promote transformations and selectivity. Inspired by nature, chemists have developed a wide range of cooperative catalytic systems by placing two or more metal centers in close proximity. Recently, a key breakthrough has been achieved that the silica-based nanoreactor with encapsulated Co III (salen) could catalyze the hydration of epoxides at H 2 O/epoxide ratio around 2 with much higher activity and high selectivity. , Therefore, porous organic frameworks with Co III (salen) have been synthesized and used for the hydration of epoxides at low H 2 O/epoxide ratio . Despite the low H 2 O/epoxide ratio and satisfying selectivity and conversion, the Co III (salen) catalysts suffer from deactivation due to the reduction of Co III to Co II .…”
Section: Introductionmentioning
confidence: 99%